Genetic Diversity of the Endangered Neotropical Cichlid Fish (Gymnogeophagus setequedas) in Brazil - Souza-Shibatta, Lenice; Kotelok-Diniz, Thais; Ferreira, Dhiego G.; Shibatta, Oscar A.; Sofia, Silvia H.; de Assumpção, Lucileine; Pini, Suelen F. R.; Makrakis, Sergio; Makrakis, Maristela C. (Frontiers in Genetics, 2018)
Gymnogeophagus setequedas is a rare and rheophilic species of tribe Geophagini, considered endangered in Brazilian red lists. Its previously known geographical distribution range was the Paraná River basin, in Paraguay, and a tributary of the Itaipu Reservoir in Brazil. Since its description no specimens have been collected in the original known distribution area. However, recent records of G. setequedas in the lower Iguaçu River, in a region considered highly endemic for the ichthyofauna, extended the known geographical distribution and may represent one of the last remnants of the species. The aim of this study was to estimate the genetic diversity and population structure of G. setequedas, using microsatellite markers and mitochondrial haplotypes, in order to test the hypothesis of low genetic diversity in this restricted population. Muscular tissue samples of 86 specimens were obtained from nine locations in the Lower Iguaçu River basin, between upstream of the Iguaçu Falls and downstream of the Salto Caxias Reservoir. Seven microsatellites loci were examined and a total of 120 different alleles were obtained. The number of alleles per locus (NA) was 17.429, effective alleles (NE) 6.644, expected heterozygosity (HE) 0.675, observed (HO) heterozygosity 0.592, and inbreeding coefficient (FIS) 0.128. Twelve haplotypes in the D-Loop region were revealed, with values of h (0.7642) and π (0.00729), suggesting a large and stable population with a long evolutionary history. Thus, both molecular markers revealed high levels of genetic diversity and indicated the occurrence of a single G. setequedas population distributed along a stretch of approximately 200 km. The pattern of mismatch distribution was multimodal, which is usually ascribed to populations in demographic equilibrium. Nevertheless, the construction of a new hydroelectric power plant, already underway between the Salto Caxias Reservoir and Iguaçu Falls, could fragment this population, causing loss of genetic diversity and population decline, and for this reason it is necessary to maintain the Iguaçu River tributaries and downstream area from the Lower Iguaçu Reservoir free of additional dams, to guarantee the survival of this species.